ПОРІВНЯЛЬНИЙ АНАЛІЗ ЕФЕКТИВНОСТІ РУХУ ТРАНСПОРТНИХ ПОТОКІВ У РАЗІ РЕАЛІЗАЦІЇ ЗЕЛЕНОЇ ХВИЛІ З УРАХУВАННЯМ ВПЛИВУ НА ДРУГОРЯДНІ ДОРОГИ - Колій, О. С.; Любий, Є. В. (Вісник Вінницького політехнічного інституту, 2025)
The article provides a detailed presentation of the results of a comprehensive study on the effectiveness of implementing coordinated traffic flow control based on the "green wave" principle. This research was conducted using microscopic simulation modelling in the SUMO environment, taking as a case study the corridor of Nauky Avenue under conditions of gradually increasing traffic intensity. The aim of the study was to comprehensively assess the feasibility of applying synchronized signal timings at urban intersections, considering not only the indicators of the main arterial road but also the changes in traffic characteristics of secondary approaches, which traditionally remain outside the focus in most studies. For this purpose, a realistic model of the transport network was built and calibrated based on an origin-destination matrix generated by the uniform probability method and refined using the TFlowFuzzy procedure with the integration of drone-based video observation data. The obtained results confirmed the hypothesis that both the "green wave" and adaptive control significantly reduce the average queue length and idle time on the main road; however, they simultaneously cause an increase in these same indicators on the secondary approaches, which in some cases offsets the overall positive effect. Considering the identified imbalance, it is recommended to use combined schemes in which adaptive or fixed "green wave" control is integrated with multicriteria optimization of traffic signal parameters, allowing for the minimization of total delays within the network and the prevention of critical deterioration in the level of service on secondary roads under high load conditions. The practical value of this work lies in the clearly formulated applicability threshold of the "green wave" depending on the ratio of main to secondary flow intensities, as well as in the proposals for integrating adaptive control algorithms under complex topologies of large cities. This provides a foundation for the further development of multicriteria optimization models and the creation of more balanced traffic management strategies.